2021
DOI: 10.3389/frsus.2021.726332
|View full text |Cite|
|
Sign up to set email alerts
|

Techno-Economic Assessment of Thermally Integrated Co-Electrolysis and Methanation for Industrial Closed Carbon Cycles

Abstract: Energy-intensive industries still produce high amounts of non-renewable CO2 emissions. These emissions cannot easily be fully omitted in the short- and mid-term by electrification or switching to renewable energy carriers, as they either are of inevitable origin (e.g., mineral carbon in cement production) or require a long-term transition of well-established process chains (e.g., metal ore reduction). Therefore, carbon capture and utilization (CCU) has been widely discussed as an option to reduce net CO2 emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…The study highlights the potential of carbon pricing to drive economic resilience and structural transformation in the face of global challenges. Böhm, Lehner, and Kienberger (2021) provide a techno-economic assessment of thermally integrated co-electrolysis and methanation processes for industrial closed carbon cycles. Their research underscores the importance of innovative technologies in reducing net CO2 emissions in energy-intensive industries that are hard to abate.…”
Section: Analyzing the Effects Of Carbon Pricing On Industrial Sector...mentioning
confidence: 99%
“…The study highlights the potential of carbon pricing to drive economic resilience and structural transformation in the face of global challenges. Böhm, Lehner, and Kienberger (2021) provide a techno-economic assessment of thermally integrated co-electrolysis and methanation processes for industrial closed carbon cycles. Their research underscores the importance of innovative technologies in reducing net CO2 emissions in energy-intensive industries that are hard to abate.…”
Section: Analyzing the Effects Of Carbon Pricing On Industrial Sector...mentioning
confidence: 99%
“…The results showed that under favorable conditions, with positive government incentives, future WWTPs could produce high-purity (>98%) propionic acid at USD 3.8 per kg, 35% less than the commercial selling value (USD 6 per kg), which was, in all cases, higher than the current selling price of biogas (USD 0.1 per m 3 ). Other research works investigated the thermo-chemical conversion of biogas and syngas, demonstrating energy efficiencies and sustainability [ 114 , 115 , 116 ].…”
Section: Techno-economic Analysis and Life Cycle Assessmentmentioning
confidence: 99%
“…Technoeconomic studies have highlighted the potential of combining SOECs CO 2 and/or H 2 O electrolysis with current chemical processes, such as Fischer-Tropsch synthesis for liquid fuels production and methanation. In this context, a recent assessment of power-to-gasoline conversion reported a gasoline price of 2.25 euros liter −1 [138] Moreover, the production of synthetic natural gas through co-electrolysis in combination with thermal integration can achieve overall electric efficiencies of >80% while via low temperature electrolysis the efficiency is limited to 60%-70% [139] However, in such studies the necessity of overcoming material degradations issues is highlighted.…”
Section: Statusmentioning
confidence: 99%